2008
DOI: 10.1021/nn800198x
|View full text |Cite
|
Sign up to set email alerts
|

Sideways Science

Abstract: In our Conversation for this issue, Klaus von Klitzing made an insightful comment about discoveries in science, and elaborated on his views.1 Great discoveries are typically not made by setting milestones, but rather by finding something unexpected along the way, realizing that it is interesting, and understanding itOas he put it, working toward a goal but then "going sideways." This was the case for his discovery of the Quantum Hall Effect as well as for many others' key breakthroughs.Each of these aspects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In the 1960s, green fluorescent protein (GFP) was purified from Aequorea victoria and its optical and structural properties were studied by Shimomura, who was awarded the Nobel Prize in Chemistry in 2008 for the discovery and development of GFP together with Chalfie and Tsien [84,85] . Investigations into the chemical structure of GFP have revealed that its green emission stems from its 4-(p-hydroxybenzylidene)imidazolidin-5-one chromophores [86,87] .…”
Section: Natural Polymersmentioning
confidence: 99%
“…In the 1960s, green fluorescent protein (GFP) was purified from Aequorea victoria and its optical and structural properties were studied by Shimomura, who was awarded the Nobel Prize in Chemistry in 2008 for the discovery and development of GFP together with Chalfie and Tsien [84,85] . Investigations into the chemical structure of GFP have revealed that its green emission stems from its 4-(p-hydroxybenzylidene)imidazolidin-5-one chromophores [86,87] .…”
Section: Natural Polymersmentioning
confidence: 99%
“…[5,15,29−31] . GFP enabled scientists to detect chemical species such as metals ions and small molecules; even to visualize processes such as the development of neurons and the migration of cancer cells [15,32,33] . Nanoparticles, such as quantum dots (QDs), gold nanoparticles, carbon dots, etc., are promising fluorescent labels for TPM [34−37] .…”
Section: Tpf Imagingmentioning
confidence: 99%